THE INFLUENCE OF WORK-LIFE BALANCE ON JOB SATISFACTION OF EMPLOYEES OF THE REGIONAL DISASTER MANAGEMENT AGENCY OF BANTEN CITY - Dina Adawiyah (Jurnal Ekonomi, 2022)
The role of work-life balance in increasing employee satisfaction at work is very important. This study was conducted to determine how much influence work-life balance has on job satisfaction of Banten City Regional Disaster Management Agency employees. This research is a quantitative study that uses primary data sources and uses questionnaires as data collection techniques. The population and samples used in this study were 32 employees of the Banten City Regional Disaster Management Agency using saturated sampling techniques. The data analysis method used is descriptive analysis, simple linear analysis, deteminant coefficient and T test hypothesis testing. The results of the analysis show that work life balance has a positive and significant effect on job satisfaction of Banten City Regional Disaster Management Agency employees. The contribution of the independent variable Work Life Balance (X) to Job Satisfaction (Y) is 0.634 or 63.4%, while the remaining 36.6% is influenced by other factors outside this study such as compensation, work safety work stress, and so on.